-4(3n-2)-n=11(n-1)

Simple and best practice solution for -4(3n-2)-n=11(n-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(3n-2)-n=11(n-1) equation:


Simplifying
-4(3n + -2) + -1n = 11(n + -1)

Reorder the terms:
-4(-2 + 3n) + -1n = 11(n + -1)
(-2 * -4 + 3n * -4) + -1n = 11(n + -1)
(8 + -12n) + -1n = 11(n + -1)

Combine like terms: -12n + -1n = -13n
8 + -13n = 11(n + -1)

Reorder the terms:
8 + -13n = 11(-1 + n)
8 + -13n = (-1 * 11 + n * 11)
8 + -13n = (-11 + 11n)

Solving
8 + -13n = -11 + 11n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-11n' to each side of the equation.
8 + -13n + -11n = -11 + 11n + -11n

Combine like terms: -13n + -11n = -24n
8 + -24n = -11 + 11n + -11n

Combine like terms: 11n + -11n = 0
8 + -24n = -11 + 0
8 + -24n = -11

Add '-8' to each side of the equation.
8 + -8 + -24n = -11 + -8

Combine like terms: 8 + -8 = 0
0 + -24n = -11 + -8
-24n = -11 + -8

Combine like terms: -11 + -8 = -19
-24n = -19

Divide each side by '-24'.
n = 0.7916666667

Simplifying
n = 0.7916666667

See similar equations:

| 7p+22=10p-80 | | 3x+15=7x | | F(x)=3x^2-5x-4 | | -9(6+4k)=23 | | x+35=130 | | x-5x^2= | | d=mb+gaforb | | f(3)=4g+6 | | (3f+6)(2f-4)=0 | | -12n-n=11n-1 | | 5y-8=5y-8 | | F(x)=2x^2+6x+5 | | 7v-17=v+7 | | 6x+20=98 | | 3x+10=8x+15 | | -16t^2-10t+3=0 | | 5x+7=130 | | 7b-66=b | | F(x)=3x^2-4x-2 | | x/69=89 | | x[2x]=24 | | 4x-20=6x | | (5+u)(5u-3)=0 | | a^2-28a+14=-192 | | 24+-5x=7x | | x^2-28a+192=0 | | 8x+5=7x+5 | | -3x+2=1x+10 | | u+13=2u | | 180d=40r+t | | n--7.6=8.9 | | 11x-x=0 |

Equations solver categories